Analisis Hukum Hak Anak Terhadap Korban Tindak Pidana Penganiayaan Anak Di Bawah Umur Ditinjau Dari Undang-Undang No. 35 Tahun 2014 - Funna, Putri Khairani; Hasibuan , Lidya Rahmadhani; Sahlepi, Muhammad Arif (Judge : Jurnal Hukum, 2024)
This research is in the form of a legal analysis of children's rights which need to be considered in the final decision in cases of criminal acts of sexual abuse against perpetrators of criminal acts of sexual abuse. Which in Decision no. 640/Pid.Sus/2023/PN Mdn child victims did not get their rights in the decision and thus the result of the judge's decision in the form of a 13 year prison sentence was not in accordance with legal provisions because the results of the decision were unfair without considering the rights of children who were victims in criminal act, the judge hereby does not consider Law no. 35 of 2014 which explains the rights of children who are victims of criminal acts. This research was carried out using a descriptive approach with qualitative methods with a normative juridical research type based on secondary data sources taken from case studies of court decisions and laws with analysis using related legal materials.